THE CORRELATION BETWEEN MOTIVATION AND ENGLISH LANGUAGE SKILLS ACHIEVEMENT OF THE ENGLISH DEPARTMENT STUDENTS - Kusumo, Romualdus Probo (Journal of English Department WM, 2013)
It is widely acknowledged that motivation has an important role in the process of learning. Motivation is a desire to achieve a goal combined with energy to work toward a goal. The students will learn the subject matter well if they have a motivation to learn. From the two types of motivation, instrumental and integrative, motivation carries the students to achieve their goals in learning English. However, to achieve the goals in learning English, the students should master English. Therefore, the writer conducted this research to see the correlation between motivation and English language skills achievement in the English Department. Then, the purpose of the research was to find out whether there is a significant correlation between motivation and English language skills achievement. The correlation research was conducted with the assistance of a motivation checklist and English language skills test as the instruments. Twenty eight respondents, who were the students of the English Department, took part in the research. They participated in responding to motivation checklist and giving their English language skills achievement. The data obtained were correlated using Product Moment Correlation formula by Pearson. The findings showed that there is a low negative correlation between motivation and English language skills achievement. It means when motivation is high, the English language skills achievement is low and vice versa. Motivation is not the only factor which affects English language skills achievement. There are other factors that also affect English language skills achievement. And through the research, the writer suggests that in the future, there should be more studies regarding the other factors that affect the English achievement.